SEPUTAR PERSOALAN PELAYANAN WAKAF DI KANTOR URUSAN AGAMA (KUA) KECAMATAN KELING KABUPATEN JEPARA - Saekhu Saekhu (Economica: Jurnal Ekonomi Islam, 2014)
Religious Affairs Office (KUA) Keling Sub-district as a facilitator of social and religious organizations officially designated by the government cannot be separated from the problems associated with land endowments. Besides Indonesian Waqf Board as the official agency of the government in charge of the waqf in Indonesia cannot be autonomous in terms of organization and management of these institutions due to lack of budget provided by the state to BWI and the lack of state budget is one of the factors of weak existing management system at BWI. This study is a descriptive kualitative analysis and includes field research (field Research). Methods of data collection using interview techniques, observation, observation and documentation, while wearing his approach and juridical and normative approach using inductive data analysis.The results of this study that waqf ministry of Religious Affairs in the Office of the District Rivet is still a lack of human resources in the field do not affect the maximum donation that endowments services provided to the public. In general ministry of waqf in the Office of Religious Affairs does not affect the level of economic welfare of the people, this happens because of the cult and the management of waqf in District Rivet still traditional individual and yet professional. In other words endowments administrative services submitted to the Office of Religious Affairs (KUA) will Keling Sub-district, but the management and supervision of the Nazarenes submitted to the village.